The Role and Importance of Community Optometrists in India - BA, Yashwath; Patnaik, Priyanka; Sushant Kumar Khah (Gayaku Publisher, 2024)
Community optometry has become a vital component of India’s healthcare system, focusing on reducing preventable visual impairment and blindness, particularly among underserved populations. With approximately 270 million people affected by vision problems, there is a crucial need for accessible primary eye care. Community optometrists serve as frontline health professionals, providing services ranging from refractive error correction to ocular disease screening, and play a key role in bridging the urban-rural healthcare gap. This article explores how community optometrists contribute to public health in India by reducing preventable blindness, supporting national initiatives like the National Programme for Control of Blindness (NPCB), and emphasizing the importance of strengthening community optometry to achieve equitable eye care. Despite challenges such as limited awareness, workforce shortages, and inadequate infrastructure, community optometry remains essential for promoting equitable eye health across India.